Metafísica, teologia e teoria social : a teoria crítica entre Theodor W. Adorno e Max Horkheimer - Deivisson Oliveira Silva (2023)
This thesis investigates the opposition between the theoretical programs of Theodor W. Adorno and Max Horkheimer, having as a guiding principle to explain the link between the motive of ‘solidarity with metaphysics’ and the antagonistic social totality, in the former, and the theology of longing and the administered world, at last. It is argued that this difference stems from two reasons: the difference in the critique of idealism and the consequent claim of materialism; and the variation in the way of conceptualizing the consolidation and reproduction of the social totality. The first chapter is dedicated to exposing the materialist position and the respective critique of idealism in each author. The second presents the approach of theological themes in the 1930s. At this point, it presents both Adorno’s critique of Søren Kierkegaard and the debate with Walter Benjamin around Franz Kafka’s work - in which his conception of ‘Inverse’ Theology is exposed - and Horkheimer’s critique of metaphysics and religion. The third is dedicated to exposing the social theory of each author and approaches the concept of ‘administered world’ in Horkheimer and of ‘antagonistic totality’ in Adorno. Finally, the last chapter examines the late work of the authors and shows the bond between their respective conceptions of the theory of society and the use of criticism and salvation of metaphysics, in Adorno, and the reason for the theological longing, in Horkheimer.